2020
DOI: 10.1002/cpt.1882
|View full text |Cite
|
Sign up to set email alerts
|

The Implausibility of Neonatal Opioid Toxicity from Breastfeeding

Abstract: The belief that newborns can develop opioid toxicity from breastfeeding is widely held but supported by very little data. Based largely on a single, highly publicized case report (the “Toronto case”), major health agencies worldwide now caution against codeine use by nursing mothers. As a result, “stronger” opioids with greater abuse liability are increasingly prescribed in its place, potentially to the detriment of maternal health. We re‐examine aspects of this case report to demonstrate why such an occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 32 publications
1
35
1
Order By: Relevance
“…One death associated with codeine in the United States has led to advisories discouraging its use in breastfeeding women. However, recent reviews have successfully documented the implausibility of this case report 6 . Hydrocodone has been the primary opioid used postnatally in the United States for decades, with good outcomes.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…One death associated with codeine in the United States has led to advisories discouraging its use in breastfeeding women. However, recent reviews have successfully documented the implausibility of this case report 6 . Hydrocodone has been the primary opioid used postnatally in the United States for decades, with good outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…However, recent reviews have successfully documented the implausibility of this case report. 6 Hydrocodone has been the primary opioid used postnatally in the United States for decades, with good outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jonathan Zipursky and David Juurlink from the University of Toronto published a paper in the journal Clinical Pharmacology and Therapeutics calling into question that newborns can develop opioid toxicity from breastfeeding. 5 In the paper they re-examined aspects of this case report and strongly argued why such an occurrence is highly implausible. 5 They concluded that: .…”
mentioning
confidence: 96%